ADOLSCENCE : GENERATION UNDER PRESSURE - CONGER, JOHN (MULTIMEDIA PUBLICATIONS INC., 1979)
A book that gives the real facts about adolescence, demolishing myths, modifying the picture of drug - dominated. pop-crazed promiscuity easily accepted by adults, ' telling it like it is' - a dauntingly difficult reaching out for values and understanding.
Keywords: CHILD AND ADOLESCENT DEVELOPMENT